Evaluasi Film sebagai Sarana Pengembangan Identitas Diri Siswa SMP/MTs - Fazli, M.; F, Firman; N, Netrawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Adolescence is a critical stage in the formation of self-identity, where junior high school students begin to explore values, interests, and social roles. Film media, as a form of strong visual communication, has great potential in supporting the development of students’ self-identity. This study aims to evaluate how film can be an educational and reflective medium in the process of forming self-identity. The method used is a literature study with a descriptive-qualitative approach, by analyzing various studies, scientific articles, and theories of adolescent development. The results of the study indicate that films that have adolescent characters, positive values, and reflective narratives can improve students’ understanding of identity, life values, and future goals. The use of film in educational activities, especially guidance and counseling, can be an effective strategy in building students’ self-awareness and empathy.